Impact of monitoring on detection of arrhythmia recurrences in the ESC-EHRA EORP atrial fibrillation ablation long-term registry. Issue 12 (13th August 2019) - Balabanski, Tosho; Brugada, Josep; Arbelo, Elena; Laroche, Cécile; Maggioni, Aldo; Blomström-Lundqvist, Carina; Kautzner, Josef; Tavazzi, Luigi; Tritto, Massimo; Kulakowski, Piotr; Kalejs, Oskars; Forster, Tamas; et al.
Abstract: Aims: Monitoring of patients after ablation had wide variations in the ESC-EHRA atrial fibrillation ablation long-term (AFA-LT) registry. We aimed to compare four different monitoring strategies after catheter AF ablation. Methods and results: The ESC-EHRA AFA-LT registry included 3593 patients who underwent ablation. Arrhythmia monitoring during follow-up was performed by 12-lead electrocardiogram (ECG), Holter ECG, trans-telephonic ECG monitoring (TTMON), or an implanted cardiac monitoring (ICM) system. Patients were selected to a given monitoring group according to the most extensive ECG tool used in each of them. Comparison of the probability of freedom from recurrences was performed by censored log-rank test and presented by Kaplan–Meier curves. The rhythm monitoring methods were used among 2658 patients: ECG ( N = 578), Holter ECG ( N = 1874), TTMON ( N = 101), and ICM ( N = 105). A total of 767 of 2658 patients (28.9%) had AF recurrences during follow-up. Censored log-rank test discovered a lower probability of freedom from relapses, which was detected with ICM compared to TTMON, ECG, and Holter ECG ( P < 0.001). The rate of freedom from AF recurrences was 50.5% among patients using the ICM while it was 65.4%, 70.6%, and 72.8% using the TTMON, ECG, and Holter ECG, respectively. Conclusion: Comparing all main electrocardiographic monitoring methods in a large patient sample, our results suggest that post-ablation recurrences of AF are significantly underreported by TTMON, ECG, and Holter ECG. The ICM estimates AF ablation recurrences most reliably and should be a preferred mode of monitoring for trials evaluating novel AF ablation techniques.